Co-producing an urban heat climate service for UK cities: A case study of Belfast, Northern Ireland - Victoria Ramsey; Claire Scannell; Tyrone Dunbar; Michael Sanderson; Jason A. Lowe (Climate Services, 2024)
UK city decision makers in local governments are coming under increasing pressure to plan for extreme heat events due to the increasing frequency and intensity of such events. While these local authorities are aware of the potential impacts of climate change, many highlight the need for more robust evidence of local climate risks to inform climate planning. Characterising the current and future spatial variability of heat risks can help city decision makers identify vulnerable populations, inform planning, and prioritise action. This paper explores the co-development of a prototype urban heat climate service for UK cities with stakeholders in the pilot city of Belfast, Northern Ireland. This two-tier service uses the latest high-resolution UK Climate Projections to assess changes in impact relevant heat indicators summarised in a bespoke set of factsheets for building awareness (Tier 1). Tier 2 combines this information with socio-economic and built environment data to provide geospatial, decision-relevant, heat risk information at the sub-city scale using a Heat Vulnerability Index (HVI) and communicated using StoryMaps. This work highlights the importance of considering the different components of risk (hazard, sensitivity and adaptive capacity) when planning interventions for extreme heat to ensure local vulnerabilities are adequately addressed. It also highlights the minimum level of heat risk to which we are now committed locally under current emission pledges. This work also explores the lessons learnt in co-production, the impact this service has had on local decision making and explores options for upscaling.